Epstein-Barr Virus-Associated γδ T-Cell Lymphoproliferative Disorder Associated With Hypomorphic IL2RG Mutation - Tanita, Kay; Hoshino, Akihiro; Imadome, Ken-Ichi; Kamiya, Takahiro; Inoue, Kento; Okano, Tsubasa; Yeh, Tzu-wen; Yanagimachi, Masakatsu; Shiraishi, Akira; Ishimura, Masataka; Schober, Tilmann; Rohlfs, Meino; et al. (Frontiers in Pediatrics, 2019)
Chronic active Epstein-Barr virus (EBV) infection (CAEBV) is an EBV-associated lymphoproliferative disease characterized by repeated or sustainable infectious mononucleosis (IM)-like symptoms. EBV is usually detected in B cells in patients who have IM or Burkitt’s lymphoma and even in patients with X-linked lymphoproliferative syndrome, which is confirmed to have vulnerability to EBV infection. In contrast, EBV infects T cells (CD4+ T, CD8+ T, and γδT) or NK cells mono- or oligoclonally in CAEBV patients. It is known that the CAEBV phenotypes differ depending on which cells are infected with EBV. CAEBV is postulated to be associated with a genetic immunological abnormality, although its cause remains undefined. Here we describe a case of EBV-related γδT-cell proliferation with underlying hypomorphic IL2RG mutation. The immunological phenotype consisted of γδT-cell proliferation in the peripheral blood. A presence of EBV-infected B cells and γδT cells mimicked γδT-cell-type CAEBV. Although the patient had normal expression of CD132 (common γ chain), the phosphorylation of STAT was partially defective, indicating impaired activation of the downstream signal of the JAK/STAT pathway. Although the patient was not diagnosed as having CAEBV, this observation shows that CAEBV might be associated with immunological abnormality.